Adjuvant atezolizumab in Japanese patients with resected stage IB‐IIIA non‐small cell lung cancer (IMpower010). Issue 12 (21st September 2022) - Kenmotsu, Hirotsugu; Sugawara, Shunichi; Watanabe, Yasutaka; Saito, Haruhiro; Okada, Morihito; Chen‐Yoshikawa, Toyofumi Fengshi; Ohe, Yuichiro; Nishio, Wataru; Nakagawa, Shizuka; Nagao, Haruka
Abstract: The global phase 3 IMpower010 study evaluated adjuvant atezolizumab versus best supportive care (BSC) following platinum‐based chemotherapy in patients with resected stage IB–IIIA non‐small cell lung cancer (NSCLC). Here, we report a subgroup analysis in patients enrolled in Japan. Eligible patients had complete resection of histologically or cytologically confirmed stage IB (tumors ≥4 cm)–IIIA NSCLC. Upon completing 1–4 cycles of adjuvant cisplatin‐based chemotherapy, patients were randomized 1:1 to receive atezolizumab (fixed dose of 1200 mg every 21 days; 16 cycles or 1 year) or BSC. The primary endpoint of the global IMpower010 study was investigator‐assessed disease‐free survival, tested hierarchically first in patients with stage II–IIIA NSCLC whose tumors expressed programmed death‐ligand 1 (PD‐L1) on ≥1% of tumor cells, then in all randomized patients with stage II–IIIA NSCLC, and finally in the intention‐to‐treat (ITT) population (stage IB–IIIA NSCLC). Safety was evaluated in all patients who received atezolizumab or BSC. The study comprised 149 enrolled patients in three populations: ITT ( n  = 117; atezolizumab, n  = 59; BSC, n  = 58), all‐randomized stage II–IIIA ( n  = 113; atezolizumab, n  = 56; BSC, n  = 57), and PD‐L1 tumor cells ≥1% stage II–IIIA ( n  = 74; atezolizumab, n  = 41; BSC, n  = 33). At the data cutoff date (January 21, 2021), a trend toward disease‐free survival improvement with atezolizumab vs BSC was observed in the PD‐L1 tumor cells ≥1% stage II–IIIA (unstratified hazard ratio [HR], 0.52; 95% confidence interval [CI], 0.25–1.08), all‐randomized stage II–IIIA (unstratified HR, 0.62; 95% CI, 0.35–1.11), and ITT (unstratified HR, 0.61; 95% CI, 0.34–1.10) populations. Atezolizumab‐related grade 3/4 adverse events occurred in 16% of patients; no treatment‐related grade 5 events occurred. Adjuvant atezolizumab showed disease‐free survival improvement and a tolerable toxicity profile in Japanese patients in IMpower010, consistent with the global study results. Abstract : This manuscript reports a subgroup analysis of Japanese patients in the global phase 3 IMpower010 study evaluating adjuvant atezolizumab vs best supportive care (BSC) following platinum‐based chemotherapy in resected stage IB‐IIIA non‐small cell lung cancer. Disease‐free survival (DFS) improvement with atezolizumab versus BSC was observed in the Japanese stage II‐IIIA population with PD‐L1 expression on ≥1% of tumor cells; in the Japanese all‐randomized stage II‐IIIA and ITT (stage IB‐IIIA) populations, unstratified DFS hazard ratios favored atezolizumab vs BSC. Adjuvant atezolizumab had a tolerable toxicity profile in Japanese patients in IMpower010, consistent with the global study results.